Economic burden of end stage renal disease: a case study in southern Iran - Habib Omranikhoo; Saeed Shabani; Atefeh Esfandiari; Hedayat Salari; Mehdi Rezaee (Health Economics Review)
Abstract Background The condition of renal failure is widely regarded as one of the most significant challenges currently facing public health and typically treated through hemodialysis. The objective of this study was to estimate the Economic burden of hemodialysis in Bushehr province and, by extension, Iran. Method This was a cross-sectional and partial economic evaluation study conducted to estimate the Economic burden of hemodialysis using the bottom-up approach in Bushehr province and, consequently Iran. Direct medical costs and the number of hemodialysis patients were attained from health information system (HIS). Indirect costs were calculated by including the cost of lost production due to hospitalization, rest at home, absenteeism from work, and also the loss of productivity due to premature death. finally, to reduce the uncertainty around the data, a two-way sensitivity analysis was carried out. Result The mean cost of hemodialysis per patient was calculated to be 169,016 $ Purchasing Power Parity (PPP) resulting in a total economic burden of hemodialysis for Bushehr province and Iran in 2022 as 13,849,321 and 977,677,441$ (which is equivalent to 0.3% Iran’s GDP) PPP respectively in 2022. The highest proportion of overall costs (52%) was attributable to indirect costs. Premature death accounted for 82.1% of this figure. While, the largest cost component within the direct costs category (57.2%) belonged to the professional and technical tariffs. Conclusion Hemodialysis imposes a significant economic burden on Iranian society. In 2022, the annual cost of hemodialysis for Iran was approximately equivalent to 0.3% of the country’s GDP. Preventive measures targeting the factors that predispose individuals to hemodialysis need to be seriously considered.